Human fronto-tectal and fronto-striatal-tectal pathways activate differently during anti-saccades - De Weijer, Antoin D.; Mandl, Rene C.; Sommer, Iris; Vink, Matthijs; Kahn, Rene S.; Neggers, Sebastiaan F. (Frontiers in Human Neuroscience, 2010)
Almost all cortical areas in the vertebrate brain take part in recurrent connections through the subcortical basal ganglia (BG) nuclei, through parallel inhibitory and excitatory loops. It has been suggested that these circuits can modulate our reactions to external events such that appropriate reactions are chosen from many available options, thereby imposing volitional control over behavior. The saccade system is an excellent model system to study cortico-BG interactions. In this study two possible pathways were investigated that might regulate automaticity of eye movements in the human brain; the cortico-tectal pathway, running directly between the frontal eye fields (FEF) and superior colliculus (SC) and the cortico-striatal pathway from the FEF to the SC involving the caudate nucleus (CN) in the BG. In an event-related fMRI paradigm participants made pro- and anti-saccades. A DTI scan was made for reconstruction of white matter tracts between the FEF, CN and SC. DTI fiber tracts were used to divide both the left and right FEF into two sub-areas, projecting to either ipsilateral SC or CN. For each of these FEF-zones an event-related fMRI timecourse was extracted. In general activity in the FEF was larger for anti-saccades. This increase in activity was lateralized with respect to anti-saccade direction in FEF zones connected to the SC but not for zones only connected to the CN. These findings suggest that activity along the contralateral FEF-SC projection is responsible for directly generating anti-saccades, whereas the pathway through the BG might merely have a gating function withholding or allowing a pro-saccade.